2017
DOI: 10.1111/odi.12637
|View full text |Cite
|
Sign up to set email alerts
|

An update of management of insomnia in patients with chronic orofacial pain

Abstract: In this review, we discuss the management of chronic orofacial pain (COFP) patients with insomnia. Diagnostic work-up and follow-up routines of COFP patients should include assessment of sleep problems. Management is based on a multidisciplinary approach, addressing the factors that modulate the pain experience as well as insomnia and including both non-pharmacological and pharmacological modalities. Parallel to treatment, patients should receive therapy for comorbid medical and psychiatric disorders, and poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Such was reflected in our participants’ considerations for improvements and ideal treatment scenarios. Since research has demonstrated the existence of a complex, bi-directional relationship which informs pain-related insomnia [ 17 , 18 , 20 , 21 , 25 , 66 , 82 – 84 ] further education and information exposure should focus on its clinical application and treatment in line with recommendations of integrated, multidisciplinary service provisions [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such was reflected in our participants’ considerations for improvements and ideal treatment scenarios. Since research has demonstrated the existence of a complex, bi-directional relationship which informs pain-related insomnia [ 17 , 18 , 20 , 21 , 25 , 66 , 82 – 84 ] further education and information exposure should focus on its clinical application and treatment in line with recommendations of integrated, multidisciplinary service provisions [ 85 ].…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral manifestations such as irritability, impatience, yawning, falling asleep during the appointment, slow body movements, and lack of interest or focus in conversation may all be indicators a patient might be experiencing chronic sleep quality issues. 3,4,24 Chronic poor sleep quality and/or quantity situations can affect facial feature appearance, the formation of oral structures, and the development of oral disease. 8,24,25,[38][39][40] Health History Assessment of a patient's health history includes information such as demographics, social history, medical history, and dental history.…”
Section: Oral Health Assessments That Identify Poor Sleep Qualitymentioning
confidence: 99%
“…3,4,24 Chronic poor sleep quality and/or quantity situations can affect facial feature appearance, the formation of oral structures, and the development of oral disease. 8,24,25,[38][39][40] Health History Assessment of a patient's health history includes information such as demographics, social history, medical history, and dental history. 19 Each piece of information regarding a patient's health, lifestyle, and cultural beliefs can help a health care provider determine the best avenues for ideal health outcomes.…”
Section: Oral Health Assessments That Identify Poor Sleep Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Different general medical comorbidities have insomnia as one of their symptoms; a condition referred to as secondary insomnia (Figure 1). Examples of these conditions are those suffering from chronic pain, such as migraine (57,58), orofacial pain (59), and musculoskeletal pain (60,61). Overall, the data from studies using different designs suggest a bidirectional and proportional association between sleep duration and pain intensity.…”
Section: Insomnia As a Manifestation Of General Medical Comorbiditymentioning
confidence: 99%